The influence of compounding process on the properties of polypropylene-cellulosic fiber nanocomposite containing nanoclay particles. - Sina Khodaparast (Regional Information Center for Science and Technology (RICeST), 2017)
The effect of compounding process applying two methods of one and two step mixing on the properties of nanocomposite is investigated. Nanocomposites were produced using polypropylene, cellulosic fibers, MAPP and nanolay as reinforcement. 1.5 and 3% MAPP and 0,2, and 4% nanoclay were used as the variable factor and 20% fibers was used. Melt flow index was measured on compounds produced using one or two steps mixing. Either compounds were mixed with fibers and MAPP and then the test specimens were made and tested according to ASTM test procedures. The results revealed that the two steps mixing increased the mechanical properties. The melt flow index of one step mixing was lower and the melt flow index of initial mixing of polypropylene with nanoclay was very high and it was reduced after compounding with fibers and MAPP. The results revealed that at higher dosages of the nanoclay tensile and bending modulus of the composite increased and tensile strength and modulus of rupture decreased.